The challenge of education: social perspectives of the teacher - Pacheco Gualdrón, Jorge Eliécer (Rastros Rostros, 2016)
Purpose: This essay reflects on the purposes of education today, on the role of teacher and student, and on the importance of the articulation between pedagogy and society. Themes: concepts of education, society, pedagogy, authority and leadership that must be present in the educational act are considered. Development: from some passages of Miguel de Unamuno’s novel: Amor y Pedagogía (Love and Pedagogy) and using the ideas of Vigotski, Franco Serrano, Bazán, among others, as reference points, some ideas on the challenges of current education are presented. Conclusions: this reflection serves to define the roles assumed by teachers and students as beings immersed in a demanding society that poses new challenges.